Exploiting biodiversity of traditional crops for mainstreaming nutrition sensitive agriculture in Nepal - Gauchan, D. (Association of Nepalese Agricultural Professionals of Americas (NAPA), 2019)
Traditional crops cultivated and consumed over generationsare important components of agrobiodiversity and support dietary diversity, productivity and livelihoods of marginalized populations in Nepal. This paper outlines the value of traditional nutrient dense crops to promote nutrition sensitive agriculture by exploiting rich biodiversity of these crops through nutrition sensitive value chain development. Use of traditional crop biodiversity for nutrition sensitive value chain development can play positive role by taking into consideration not only how diverse nutrient-dense foods are produced but also how theyare processed, distributed, marketed and consumed to supply nutrient value for household nutrition security. However, presently value chains of biodiversity of traditional crops are weak, fragmented and not properly connected among sub-components of production, processing, marketing and consumption system. Considering this, focus of biodiversity-based value chain upgrading is suggested to improve their performance, efficiency and interlinkages in different sub-components. Creating enabling policy for investment in research, education, extension and value chain development is essential to exploit rich biodiversity of traditional nutrient dense crops. Promotion of organic and ecofriendly production, marketing and certification system linking with geographic indication and fair trading is suggested for mainstreaming traditional nutrient dense crops in national policies, program and institutions.